2022
DOI: 10.3389/fcvm.2022.931219
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Cardiac Sympathetic Activity Assessment Methods: Current Knowledge

Abstract: This review has summarized the methods currently available for cardiac sympathetic assessment in clinical or under research, with emphasis on the principles behind these methodologies. Heart rate variability (HRV) and other methods based on heart rate pattern analysis can reflect the dominance of sympathetic nerve to sinoatrial node function and indirectly show the average activity level of cardiac sympathetic nerve in a period of time. Sympathetic neurotransmitters play a key role of signal transduction after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…In order to assess cardiac autonomic modulation, we performed Wavelet analysis using the Wigner-Ville transform (W-V) for time/frequency domain analysis with standard MatLab software. We determined sympathetic and parasympathetic modulation of RR intervals (RRI) in the low frequency (LF; 0.04–0.14 Hz) and high frequency (HF; 0.15–0.50 Hz) ranges ( Task Force of the European Society of Cardiology the North A, 1996 ; Hilz and Dütsch, 2006 ; Li and Zheng, 2022 ). LF modulation of RRI reflects mainly sympathetic tone and, to an undetermined degree, also parasympathetic modulation; HF oscillations of RRIs reflect parasympathetic modulation ( Task Force of the European Society of Cardiology the North A, 1996 ; Hilz and Dütsch, 2006 ; Li and Zheng, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to assess cardiac autonomic modulation, we performed Wavelet analysis using the Wigner-Ville transform (W-V) for time/frequency domain analysis with standard MatLab software. We determined sympathetic and parasympathetic modulation of RR intervals (RRI) in the low frequency (LF; 0.04–0.14 Hz) and high frequency (HF; 0.15–0.50 Hz) ranges ( Task Force of the European Society of Cardiology the North A, 1996 ; Hilz and Dütsch, 2006 ; Li and Zheng, 2022 ). LF modulation of RRI reflects mainly sympathetic tone and, to an undetermined degree, also parasympathetic modulation; HF oscillations of RRIs reflect parasympathetic modulation ( Task Force of the European Society of Cardiology the North A, 1996 ; Hilz and Dütsch, 2006 ; Li and Zheng, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…We determined sympathetic and parasympathetic modulation of RR intervals (RRI) in the low frequency (LF; 0.04–0.14 Hz) and high frequency (HF; 0.15–0.50 Hz) ranges ( Task Force of the European Society of Cardiology the North A, 1996 ; Hilz and Dütsch, 2006 ; Li and Zheng, 2022 ). LF modulation of RRI reflects mainly sympathetic tone and, to an undetermined degree, also parasympathetic modulation; HF oscillations of RRIs reflect parasympathetic modulation ( Task Force of the European Society of Cardiology the North A, 1996 ; Hilz and Dütsch, 2006 ; Li and Zheng, 2022 ). We also calculated the ratios between RRI modulations in the LF and HF ranges, using the LF/HF ratios as index of the sympathetic-parasympathetic balance ( Task Force of the European Society of Cardiology the North A, 1996 ; Hilz and Dütsch, 2006 ; Li and Zheng, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, for the screening of SAH, some clinical assessments for SA have been proved to be effective, including clinical features, neurotransmitter detection, metabolic biochemical-index detection, sympathetic-nerve-potential detection, and hemodynamic detection [ 42 ]. Studies have shown that patients who meet the following description are suggestive of the possibility of SAH, requiring further examination and early intervention: (1).…”
Section: Sympathetic-active Hypertensionmentioning
confidence: 99%
“…Regions of cardiac sympathetic nerve terminal denervation and hyperinnervation are present in the same failed heart to form the heterogeneity of the cardiac sympathetic nerve distribution [ 119 , 120 ]. Iodine-123 meta-iodobenzylguanidine ( 123 I-MIBG) or other radiolabeled neurotransmitter analogs (including the recently used F-18 meta-fluorobenzylguanidine) and cardiac neurotransmission imaging with single-photon emission computed tomography (SPECT) and positron emission tomography (PET) have been employed to noninvasively assess the integrity of human NET and further evaluate cardiac sympathetic nerve innervation [ 121 , 122 , 123 ]. However, poor imaging quality, difficulty in distinguishing different cardiac structures, and high cost limit this technique’s application in animal studies, especially small animal studies.…”
Section: Remodeling Of Cardiac Postganglionic Sympathetic Neurons And...mentioning
confidence: 99%